KALIBRASI SPASIAL CITRA RADIOGRAFI DAN KALIBRASI DOSIS MESIN SINAR X PANORAMIK GIGI - , LINA KURNIAWATI, Prof. Dr. Kusminarto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research to determine the relationship between the image and the real object by spatial calibration and measuring of radiation dose distribution of dental panoramic machine in the radiography room has been done. The spatial calibration was done by taking the image of standard measure in the form of wire in various length put vertically and horizontally at the right, middle, and left bone position on the lower jaw human bone. The result of research show that the calibrations factor of those three positions wire horizontally at A1, B1, and C1 are different wich are 8.9 Â± 0.5 pixel/mm, 7.8 Â± 0.2 pixel/mm, and 9.2 Â± 0.3 pixel/mm respectively and therefore the calibration factor of DBSWin software is 9.9 pixel/mm doesnât apply for all part of the image. The radiation dose distribution measurement was done for panoramic X-ray machine operated at voltage 80 kV, current of 10 mA, and 4 second exposure time. The higest dose found at the center position of the object being radiographed. Dose radiation of right cheek 4.6 mR/hr, left cheek 4.7 mR/hr, and the back of the head 4.9 mR/hr whereas the average dose rate was found to be 4.7 mR/hr. This suggest that the radiation dose rate on object doesnât excedd the Dose Limit Value (NBD) of Bapeten that value is 5.7 mR/hr because during the process of X-ray radiation exposure doesnât focussed on one point.Research to determine the relationship between the image and the real object by spatial calibration and measuring of radiation dose distribution of dental panoramic machine in the radiography room has been done. The spatial calibration was done by taking the image of standard measure in the form of wire in various length put vertically and horizontally at the right, middle, and left bone position on the lower jaw human bone. The result of research show that the calibrations factor of those three positions wire horizontally at A1, B1, and C1 are different wich are 8.9 Â± 0.5 pixel/mm, 7.8 Â± 0.2 pixel/mm, and 9.2 Â± 0.3 pixel/mm respectively and therefore the calibration factor of DBSWin software is 9.9 pixel/mm doesnât apply for all part of the image. The radiation dose distribution measurement was done for panoramic X-ray machine operated at voltage 80 kV, current of 10 mA, and 4 second exposure time. The higest dose found at the center position of the object being radiographed. Dose radiation of right cheek 4.6 mR/hr, left cheek 4.7 mR/hr, and the back of the head 4.9 mR/hr whereas the average dose rate was found to be 4.7 mR/hr. This suggest that the radiation dose rate on object doesnât excedd the Dose Limit Value (NBD) of Bapeten that value is 5.7 mR/hr because during the process of X-ray radiation exposure doesnât focussed on one point.